Complaints of a celebrated theologian about the fourteenth century university: Jean Gerson's critiques towards the masters and students of his time - França, Susani Silveira Lemos [UNESP]; de Almeida, Letícia Alfeu Gonçalves [UNESP] (Universidade Estadual de Maringa, 2019)
With emphasis on personal and official epistolary writings, this paper seeks to examine how a fifteenth-century theologian, the prominent chancellor of the University of Paris, Jean Gerson (1363-1429), reflected on the situation of that university, pointing out its ways and redefining or reaffirming its role in the Christian West. Based on letters addressed to authorities, fellow theologians and friends linked to such an environment, this article explores the main points about institutional and political barriers, the weaknesses of the knowledge produced there and, above all, the behavior of teachers and students who, according to the chancellor, prevented the University from fully exercise its function for the benefit of the Christian community. In short, the complaints of a doctor in theology about behaviors worthy of reprimand regarding the relationship of his peers with knowledge and his expectations about the university of his time are scanned.
Quejas de un célebre teólogo sobre la universidad del siglo XIV: Las críticas de Jean Gerson a los maestros y estudiantes de su tiempo
Queixas de um célebre teólogo sobre a universidade quatrocentista: as críticas de Jean Gerson sobre os mestres e alunos do seu tempo
Keywords: changeable masters; faculty of theology; fifteenth century; Jean Gerson; licentious students; university of Paris